2010
DOI: 10.1007/s10610-010-9124-9
|View full text |Cite
|
Sign up to set email alerts
|

Deviant Youth Groups in Italy and France: Prevalence and Characteristics

Abstract: This paper sets out to compare the existence of Juvenile deviant groups in both France and Italy and their characteristics. The comparison between Italy (N=5,236) and France (N=3, 353) is based on the ISRD study of the year 2006 and shows that the term "gang" is commonly used to refer to a group of friends only. The strongest associated variables in both countries to illegal acts are the acceptance of doing illegal things, taking part in delinquent acts, considering the group as a gang as well as spending a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 22 publications
0
16
1
Order By: Relevance
“…The questionnaire was informed by several sources including questions on deviant youth groups (DYG) from the ISRD survey (Blaya and Gatti, 2010) and some questions on digital practices from the EU Kids Online survey (Livingstone et al, 2011). The questions related to cyberhate were informed by an extensive literature review and some exploratory interviews that were conducted prior the designing of the survey.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The questionnaire was informed by several sources including questions on deviant youth groups (DYG) from the ISRD survey (Blaya and Gatti, 2010) and some questions on digital practices from the EU Kids Online survey (Livingstone et al, 2011). The questions related to cyberhate were informed by an extensive literature review and some exploratory interviews that were conducted prior the designing of the survey.…”
Section: Methodsmentioning
confidence: 99%
“…We used the questionnaire previously used by Blaya and Gatti (2010) and Livingstone et al (2011), which yielded good reliability indices (α = 0.95, ω = 0.96). It was made up of general questions about the socio-demographic characteristics of respondents and their families, their digital practices (ICT use), their experiences of bullying in schools, their satisfaction with life.…”
Section: Measurement Toolmentioning
confidence: 99%
“…In the past several years, gang researchers have expanded their focus beyond the United States to include Europe (e.g., Blaya & Gatti, 2010;Decker & Weerman, 2005;Esbensen & Weerman, 2005;Klein, Kerner, Maxson, & Weitekamp, 2001;Haymoz & Gatti, 2010;Huizinga & Schumann, 2001) and, in a much more limited way, Asia. The research reported here represents an attempt to expand the body of research on youth gangs by addressing the question of whether or not there are youth gangs and gang crime in China.…”
Section: Introductionmentioning
confidence: 99%
“…While measuring gang membership with the first six items is a strategy designed to avoid mention of the word 'gang' and has been used by some researchers to assess gang membership (e.g., Matsuda et al 2012), these items do not explicitly address the group's identity, which is also part of the Eurogang definition. Thus, other researchers have included the seventh item as a core indicator of gang membership (e.g., Blaya and Gatti 2010;Haymoz and Gatti 2010;Gatti et al 2011;Moravcová 2012). 5 'Gangs' have returned, as it were, by the back door.…”
Section: Table 1 About Herementioning
confidence: 99%
“…Although they reported some nonsignificant results -for example, gang membership was not associated with family structure -they did not discuss these in terms of construct validity. For their part, studies using ISRD-2 data have also found a higher prevalence of drug use, delinquency and victimization among those defined as gang members, but they have not discussed the findings in terms of the construct validity of the Eurogang items (e.g., Blaya and Gatti 2010;Gatti et al 2011).…”
Section: Table 1 About Herementioning
confidence: 99%